2015 38th International Spring Seminar on Electronics Technology (ISSE) 2015
DOI: 10.1109/isse.2015.7247961
|View full text |Cite
|
Sign up to set email alerts
|

Experimental 13.56 MHz RFID cards on biodegradable substrates

Abstract: The paper presents experimental research on investigating the production and testing aspects of ISO/IEC 14443 contactless RFID tags fabricated on biodegradable cellulose acetate (CA) biopolymer-based Printed Circuit Boards (PCB). Our approach reduces the harmful plastic waste by substituting the standard materials of the cards with biodegradable substrate. Also, with common PCB fabrication methodology the prototyping and production becomes cost-effective for the novel material. The paper will detail the manufa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Géczy et al showed PLA and cellulose-acetate (CA) boards could be used for surface mounting. The research group also produced several other publications, involving PLA and CA, as PCB substrate [19][20][21][22][23][24][25][26][27]. Recently a promising improvement was introduced by the same team, where flame-retarded PLA was reinforced with flame-retarded flax fibres, to form a biodegradable substrate [27].…”
Section: B Materials and Processes Used To Produce Printed Electronic...mentioning
confidence: 99%
See 1 more Smart Citation
“…Géczy et al showed PLA and cellulose-acetate (CA) boards could be used for surface mounting. The research group also produced several other publications, involving PLA and CA, as PCB substrate [19][20][21][22][23][24][25][26][27]. Recently a promising improvement was introduced by the same team, where flame-retarded PLA was reinforced with flame-retarded flax fibres, to form a biodegradable substrate [27].…”
Section: B Materials and Processes Used To Produce Printed Electronic...mentioning
confidence: 99%
“…Nevertheless, the quality of joints depends on the specific type of biopolymer [45]. Further, instead of standard bismuth-tin solder alloy (58Bi42Sn or 58Bi41Sn1Ag), Rose's alloy with the composition of 50Bi(25-28)Pb (22)(23)(24)(25)Sn can be beneficially utilized thanks to its melting point of 94 °C [17].…”
Section: Assemblingmentioning
confidence: 99%
“…They even added rice paper into their investigations. Cellulose acetate (CA) material was lately investigated as a possible substrate for RFID cards [16]. Schramm et al [17] investigated the manufacturing possibilities of the degradable materials.…”
Section: Faculty Of Electrical Engineeringmentioning
confidence: 99%
“…Due to the strict limitations and needs for green electronics, biodegradable and environmentally friendly materials are increasingly being used in the field of antennas [ 22 , 23 ]. There are substrate materials such as cellulose-acetate (CA) [ 24 ], glucopyranoside (GPTE), and diethylene-toluene-tetramine (DETDA) [ 25 ] that can be used in place of conventional polymeric substrates. The surface quality of polymeric substrates is a critical technological factor in the HF area [ 26 ].…”
Section: Introductionmentioning
confidence: 99%